2021
DOI: 10.5114/pjr.2021.103237
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of imaging findings in pulmonary hydatid disease and the additive value of T2-weighted magnetic resonance imaging in its diagnosis

Abstract: Purpose To describe the spectrum of imaging findings in pulmonary echinococcosis and to study the additive value of T2-weighted magnetic resonance imaging (MRI) in the characterisation of pulmonary hydatid disease. Material and methods This was a descriptive, prospective study conducted for a period of 3 years from December 2016 to November 2019. Patients suspected of having pulmonary echinococcosis ( n = 110) on preliminary chest radiography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…However, a complicated cyst (ruptured, infected) may resemble other pathologies on imaging, such as lung abscess or cancer. In such cases, Choh et al suggest adding T2-weighted MRI to the diagnosis process [ 21 ]. In rare cases of pleural hydatidosis, the infection may manifest as a massive pleural effusion, which is frequently of malignant origin [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a complicated cyst (ruptured, infected) may resemble other pathologies on imaging, such as lung abscess or cancer. In such cases, Choh et al suggest adding T2-weighted MRI to the diagnosis process [ 21 ]. In rare cases of pleural hydatidosis, the infection may manifest as a massive pleural effusion, which is frequently of malignant origin [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Naseer, et al reported chest CT characteristics for hydatid cysts from 84 patients. 12 The characteristic is a hypodense cyst with a well-defined perceptible cyst wall with normal surrounding parenchyma (21.4%) or consolidation (34.6%). Radiological signs of hydatid cysts can be categorized as uncomplicated or difficult, depending on whether there are problems such as rupture, complete rupture, or superinfection.…”
Section: Discussionmentioning
confidence: 99%
“…The lung cancer and non-COVID-19 lung infections image dataset was developed using multiple reliable free online access public chest CT examinations: Radiopaedia (pneumonia [ 41 ], lung abscess [ 42 ], lung hydatid infection [ 43 ], tuberculosis [ 44 ], primary lung cancer [ 45 ], pulmonary metastases [ 46 ]) and the COVID-19 and common pneumonia chest CT dataset (412 common pneumonia CT scans) [ 47 ]. Morever, this dataset also included a large-scale CT and PET/CT dataset for lung cancer diagnosis (Lung-PET-CT-Dx) [ 48 ], as well as chest CT scans from the internal PACS of the Medical Imaging Department at the University of Medicine and Pharmacy of Craiova.…”
Section: Methodsmentioning
confidence: 99%